2019
DOI: 10.1016/j.nepr.2019.102625
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical principles and methods underpinning education of health and social care practitioners on experiences and needs of older LGBT+ people: Findings from a systematic review

Abstract: and Keogh, Brian (2019) Pedagogical principles and methods underpinning education of health and social care practitioners on experiences and needs of older LGBT+ people: findings from a systematic review. Nurse Education in Practice, 40 , 102625.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 58 publications
3
60
0
Order By: Relevance
“…There may be concerns about students being unwilling to participate due to religious beliefs. [16][17][18][19][20] Many faculty do not consider themselves experts and may not feel qualified to teach about this topic due to their own limited training. 4,5,19 Finally, uncertainty regarding which LGBTQIA+ topics should be covered may prevent pharmacy schools from integrating the content, especially when competing with tier one and two topics.…”
Section: Barriers To Integration Into Pharmacy School Curriculamentioning
confidence: 99%
See 1 more Smart Citation
“…There may be concerns about students being unwilling to participate due to religious beliefs. [16][17][18][19][20] Many faculty do not consider themselves experts and may not feel qualified to teach about this topic due to their own limited training. 4,5,19 Finally, uncertainty regarding which LGBTQIA+ topics should be covered may prevent pharmacy schools from integrating the content, especially when competing with tier one and two topics.…”
Section: Barriers To Integration Into Pharmacy School Curriculamentioning
confidence: 99%
“…4,5,7,11 Addressing Religious Objections Students may be unwilling to participate in lectures and activities related to LGBTQIA+ content due to conflicting religious views. 16,19 Carabez et al found that more than 1 in 10 nursing students reported religious values that may interfere with the quality of care of transgender patients. 18 Mandatory training may not lead to a change in attitudes or behaviors, and some individuals may still refuse to attend.…”
Section: Barriers To Integration Into Pharmacy School Curriculamentioning
confidence: 99%
“…Where LGBT+ older adults were involved (in person or video) in telling their personal stories, participants reported enhanced engagement with the intervention, greater awareness of LGBT+ issues and increased empathy (Gendron et al., 2013; Hughes et al., 2016; Leyva et al., 2014; Pelts & Galambos, 2017; Rogers et al., 2013). The inclusion of older LGBT+ adults in the intervention design and delivery is a strategy that is now recognized as a core principle underpinning the provision of education to health and social care practitioners on LGBT+ older adults (Cannon et al., 2017; Higgins, Downes, Sheaf, et al, 2019; Higgins, Keogh, et al, 2019). While the relationship between the degree of citizen involvement and the outcomes has yet to be researched, the inclusion of LGBT+ older adults is of significance, given the importance placed on patient and public involvement and co‐production within health and social care policy and practice (Ocloo & Matthews, 2016; Sapouna, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Past research highlights that applying a gender-sensitive perspective in patient-centered care requires that clinicians understand gender differences, issues, inequalities and incorporate these into strategies and actions [5,6]. Several researchers argue that service providers who ignore the sexuality and gender identity of clients often fail to deliver person-centered care [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlighted the delivery method of the gender-sensitive care training that participants wanted, which included having a variety of options (e.g., online training, workshops, informal discussions, and learning from patient's lived experience). Given the complexity of gender-sensitivity, having multi-level training while using an interactive pedagogical approach is more likely to promote gender-sensitivity [65]. Although many educators recognize a need for gender-sensitive healthcare training, of the places that offer it, it is usually an optional course within postgraduate education [3].…”
Section: Discussionmentioning
confidence: 99%